(untitled) (The Transactions of the Nigerian Association of Mathematical Physics, 2024)
In this paper, we develop a discrete time Economic Order Quantity (EOQ) Model with constant demand for items that are ameliorating. In the model, the items considered are assumed to ameliorate immediately they arrive in stock. The purpose is to determine the optimal ordering quantity and replenishment cycle so as to minimize the total variable cost. It is the remodelling of Gwanda by considering time to be discrete. The model is developed using difference equation with initial and boundary conditions. Numerical examples are illustrated to see the application of the model and sensitivity analysis carried out to determine the effect of the parameter changes.